2021
DOI: 10.1371/journal.pone.0255323
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota alterations in response to sleep length among African-origin adults

Abstract: Sleep disorders are increasingly being characterized in modern society as contributing to a host of serious medical problems, including obesity and metabolic syndrome. Changes to the microbial community in the human gut have been reportedly associated with many of these cardiometabolic outcomes. In this study, we investigated the impact of sleep length on the gut microbiota in a large cohort of 655 participants of African descent, aged 25–45, from Ghana, South Africa (SA), Jamaica, and the United States (US). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 106 publications
2
22
0
3
Order By: Relevance
“…[146] Gut microbiome status including altered metabolism affects sleep. [147] Probiotic supplementation improved sleep among postoperative cancer patients. [148] Sleep quality improved with a probiotic complex.…”
Section: Details Reference(s)mentioning
confidence: 99%
“…[146] Gut microbiome status including altered metabolism affects sleep. [147] Probiotic supplementation improved sleep among postoperative cancer patients. [148] Sleep quality improved with a probiotic complex.…”
Section: Details Reference(s)mentioning
confidence: 99%
“…In Africa, urbanization, dietary patterns, obesity, decreasing physical activity, increasing alcohol consumption, and fertility transitions, characterized by delayed or decreased childbearing, have been implicated in the increasing incidence of cancers. 9-11 …”
Section: Cancer Burden In Africamentioning
confidence: 99%
“…12 HPV infection is known to be the primary cause of cervical cancer among sexually active women in Ghana. 9 …”
Section: Cancer Burden In Ghanamentioning
confidence: 99%
“…Much like the observation that NCDs are often linked to socioeconomic position—such that NCDs are disproportionally shouldered by the disadvantaged—research has shown that the composition and diversity of gut (and oral) microbes are similarly associated with socioeconomic position in various populations [ 75 , 76 , 77 , 78 , 79 ]. It is also known that functional changes to the microbiome are mediated by many “lifestyle” factors, including stress [ 80 , 81 , 82 ], sleep [ 83 ], exercise [ 84 ], tobacco use [ 85 ], and, of course, short and long-term dietary choices [ 86 , 87 , 88 ].…”
Section: New Perspectives On the Ecology Of Social Disadvantagementioning
confidence: 99%